The effects of internet on international marketing communications - Pouresmaeili, Hamideh; Nezakati, Hossein *; Mehdizadeh, Abbas (2010)
Purpose- The main purpose of this article is to provide a clear perceptive about the effect of Internet as a major mean of communication on international marketing, and understanding the benefits and challenges that a company will face in a global market through online business. In order to achieve this purpose, this paper is organized in the following sections: introduction, revolution of communication, international marketing and communication, and choosing media to change the marketing world with technology. Following by communication tools, and explanation on E-Business, E-Marketing, and E-Commerce. In the next section, Impact of Internet and changing of marketing mix face, benefits of going online, and the issues in marketing via Internet will be discussed, and finally the conclusion of the paper.